DIALECTICAL INVOLVEMENT OF ECOLOGICAL CULTURE AND MORAL AND AESTHETIC EDUCATION - Tolliboev, Dilshod; Kushmanov, Jamoliddin (Journal of Contemporary World Studies, 2023)
There are a number of tools that shape, strengthen and harmonize ecological, moral and aesthetic education. They decide on the basis of a creative approach, inextricably linked with the moral and aesthetic educational foundations of nature. The degree of moral or aesthetic attitude towards nature is also felt from the behavior, attitudes of people. Morality is the greatest wealth in the treasury of the human soul.